Rising burden of subarachnoid hemorrhage linked to high systolic blood pressure among young and middle-aged populations: temporal trends and global implication - Chen, Pengfei; Chen, Junlin; Liu, Jiazuo (Frontiers in Human Neuroscience, 2025)
BackgroundSubarachnoid hemorrhage (SAH) is a devastating cerebrovascular event that leads to high mortality and long-term disability, particularly among adults aged 25–49 years. Elevated systolic blood pressure (SBP) is the leading modifiable risk factor, yet its global burden in this age group has not been systematically assessed.MethodsWe analyzed population-level epidemiological data across 204 countries and territories from 1990 to 2021 to estimate SAH mortality and disability-adjusted life-years (DALYs) attributable to high SBP. Temporal trends were evaluated using estimated annual percentage change (EAPC), and future trajectories to 2050 were projected with autoregressive integrated moving average (ARIMA) models.ResultsGlobally, SAH caused 24,908 deaths and 1,373,366 DALYs in 2021 due to high SBP in adults aged 25–49 years. Males had higher rates than females (mortality: 0.78 vs. 0.48 per 100,000; DALYs: 42.4 vs. 27.0 per 100,000), though females experienced steeper declines (EAPC_mortality: −1.78%). The highest burden was in the 45–49 age group (deaths: 9,768; DALYs: 474,092). From 1990 to 2021, high-SDI regions achieved the greatest reductions in mortality (−50.3%) and DALYs (−46.8%), while low-SDI regions saw increases in deaths (+109.5%) and DALYs (+114.7%). Nationally, Zimbabwe and Guatemala showed the sharpest increases in mortality (EAPC: +4.71% and +3.76%), while Sweden and Swiss Confederation achieved the greatest declines (EAPC: −5.5% and −4.9%). Forecasts suggest continued global declines by 2050, but widening disparities by sex, age, and socio-demographic status.ConclusionAlthough the global burden of SAH attributable to high SBP is decreasing, young and middle-aged adults-especially males and those in low-SDI regions-continue to face substantial risks. Targeted hypertension control and region-specific prevention strategies are urgently needed.